2019
DOI: 10.1016/j.ajur.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of fluorescence in situ hybridization in the detection of bladder transitional-cell carcinoma: A multi-center clinical study based on Chinese population

Abstract: ObjectiveTo evaluate the diagnostic value of fluorescence in situ hybridization (FISH) in bladder cancer.MethodsWe enrolled healthy volunteers and patients who were clinically suspected to have bladder cancer and conducted FISH tests and cytology examinations from August 2007 to December 2008. Receiver operating characteristic (ROC) curve analysis was performed and the area under curve (AUC) values were calculated for both the FISH and urine cytology tests.ResultsA cohort of 988 healthy volunteers was enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Zhou L et al23 are comparable to our results (30%, 91% & 86%). Another study conducted by Bier S. et al24 included 758 bladders and 385 upper urinary tract (UUT) samples, the sensitivity of cytology & NMP 22 were found 74.6 & 100% for UUT and 59.3 & 62.5% for bladder samples while specificity was 66.6 & 50.9% for UUT and 82.9 & 31.3 for bladder samples.…”
supporting
confidence: 92%
“…Zhou L et al23 are comparable to our results (30%, 91% & 86%). Another study conducted by Bier S. et al24 included 758 bladders and 385 upper urinary tract (UUT) samples, the sensitivity of cytology & NMP 22 were found 74.6 & 100% for UUT and 59.3 & 62.5% for bladder samples while specificity was 66.6 & 50.9% for UUT and 82.9 & 31.3 for bladder samples.…”
supporting
confidence: 92%
“…The chromosome 9p21 region (p16) gene deletion rate was only 14.29% (1/7). However, in a multicenter big data study conducted by Zhou et al ( 10 ) in China, the polysomy of chromosomes 3, 7, and 17 and gene changes at 9p21 region (p16) accounted for 71.3% (2941/4125), 72.2% (2978/4125), 67.4% (2780/4125), and 72.9% (3007/4125) of urothelial carcinoma cases, respectively. Therefore, the chromosome 9p21 region (p16) gene deletion in urachal carcinoma seems to occur less frequently than in urothelial carcinoma (16.67 vs. 72.9%, P = 0.008).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have evaluated the efficacy of FISH in urothelial carcinoma ( 5 10 ), whereas data on the evaluation of UroVysion probes in non-urothelial carcinoma are scarce. This study found that the positive rate of FISH in urachal carcinoma of late stage with hematuria was rather high at 71.43%, which was not significantly different from that in urothelial carcinoma (71.43 vs. 87.18%, P = 0.245).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With fluorescence in situ hybridization (FISH) techniques, chromosomal anomalies can be detected in exfoliated bladder cells. Several studies reported low sensitivity of FISH to detect low-grade (36%-57%) and low-stage (62%-65%) tumors, while has high sensitivity for both high-grade and high-stage tumors (83%-97%) [4,5]. The detection of CIS is close to 100% and its hight specificity (89%-96%) is comparable to cytology [6].…”
Section: Molecular Markers In Bcamentioning
confidence: 99%